A Validated LC Method for the Quantitation of Cefotaxime in pH-Sensitive Nanoparticles - Rosa Pereira (2010)
A sensitive and rapid routine LC method was validated for measuring cefotaxime incorporated in three different pH-sensitive nanoparticles. The drug was chromatographed on a C18 reversed-phase column; the mobile phase used was 0.05 M aqueous ammonium acetate, acetonitrile and tetrahydrofuran (87:11:2, v/v) adjusted to pH 5.5 with acetic acid. The flow rate was 1 mL min(-1) and cefotaxime was quantified at 254 nm, with a sensitivity range of 0.005 AUFS. The validated method was specific, linear (R (2) a parts per thousand yen 0.999), precise and accurate in a concentration range of 0.2-50.0 mu g mL(-1). The method was rapid, selective and suitable for evaluation of cefotaxime in pH-sensitive Eudragit nanoparticles.